Development e-report character model for elementary school students to increase the effectiveness of assessment - Winayu, Isnaeni Machra; Danim, Sudarwan; Hamzah, Syukri; Kristiawan, Muhammad; Diharja, Umar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The development of student character in integrated Islamic schools, which combine the Muslim personality-oriented Islamic Education Curriculum with the National Curriculum for behavioral assessment on report cards, is of paramount importance. This article focuses on the building of a practical and effective web-based character report card for elementary school children. This research utilized the 4 D methodology of Research & Development (R&D), including define, design, develop, and disseminate. The research findings on the development of e-report applications indicated a validity assessment by media professionals, yielding a score of 85.75%, categorizing it as highly practical. Evaluate the product's practicality with the t-test, which revealed that inputting values in the e-report application was more efficient than manual entry. The effectiveness is evidenced by the teacher's response, which garnered a positive evaluation with a score of 85.60%, categorizing it as very good. Utilizing web-based e-reports for processing assessments aids educators in effectively managing practical character behavior report scores for each assessment indicator description.